2022
DOI: 10.3390/brainsci12081095
|View full text |Cite
|
Sign up to set email alerts
|

Functional Connectivity Increases in Response to High-Definition Transcranial Direct Current Stimulation in Patients with Chronic Disorder of Consciousness

Abstract: High-definition transcranial direct current stimulation (HD-tDCS) has been shown to play an important role in improving consciousness in patients with disorders of consciousness (DOCs), but its neuroelectrophysiological evidence is still lacking. To better explain the electrophysiological mechanisms of the effects of HD-tDCS on patients with DOCs, 22 DOC patients underwent 10 anodal HD-tDCS sessions of the left dorsolateral prefrontal cortex (DLPFC). This study used the Coma Recovery Scale-Revised (CRS-R) to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Hermann found that the theta–alpha PO connectivity was a reliable marker of improved consciousness in tDCS responders targeting the DLPFC 46 . A similar study also found that the changes in left frontal‐parieto‐occipital theta connectivity were positively correlated with the changes in CRS‐R scores after high‐definition tDCS (HD‐tDCS) intervention 47 . In contrast, a study used HD‐tDCS targeting the precuneus as a treatment for patients with DOC and revealed that improved consciousness was accompanied by an increase in mean PO connectivity in the beta band and the whole brain in the gamma band 48 .…”
Section: Discussionmentioning
confidence: 88%
“…Hermann found that the theta–alpha PO connectivity was a reliable marker of improved consciousness in tDCS responders targeting the DLPFC 46 . A similar study also found that the changes in left frontal‐parieto‐occipital theta connectivity were positively correlated with the changes in CRS‐R scores after high‐definition tDCS (HD‐tDCS) intervention 47 . In contrast, a study used HD‐tDCS targeting the precuneus as a treatment for patients with DOC and revealed that improved consciousness was accompanied by an increase in mean PO connectivity in the beta band and the whole brain in the gamma band 48 .…”
Section: Discussionmentioning
confidence: 88%
“…Sample size estimation was conducted using G*Power software. The effect size value was calculated based on previous similar studies ( Han et al, 2022b ), with f = 0.47, α= 0.05, and power (1-β) = 0.95. Considering a potential participant attrition rate of 20%, the total sample size was determined to be 90 cases.…”
Section: Methodsmentioning
confidence: 99%
“…There is growing evidence from non-invasive intervention studies that DLPFC stimulation can modulate RSFC [27][28][29][30][31]. An early study on healthy controls, reported that one tDCS session stimulating bilateral DLPFC modulated RSFC of the default mode, fronto-parietal, and interceptive networks [32].…”
Section: Effect Of Dlpfc Stimulation On Rsfcmentioning
confidence: 99%